2015
DOI: 10.1016/j.wasman.2015.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Does vegetation affect the methane oxidation efficiency of passive biosystems?

Abstract: It is often reported in the technical literature that the presence of vegetation improves the methane oxidation efficiency of biosystems; however, the phenomena involved and biosystem performance results are still poorly documented, particularly in the field. This triggered a study to assess the importance of vegetation in methane oxidation efficiency (MOE). In this study, 4 large scale columns, each filled with sand, topsoil and a mixture of compost and topsoil were tested under controlled conditions in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
2
Order By: Relevance
“…This seems to indicate that θ a_occ could potentially be inferred from the optimum water content determined from the Standard Proctor test (ASTM D6-8 -12e2). However, for another substrate (fine sand) also successfully employed as MOL (Ndanga et al, 2015), Ahoughalandari et al (2018) found that the S r value associated with occlusion was greater than that given by the line of optima. As such, the simplification proposed, i.e.…”
Section: Design Steps Based On Hydraulic Considerationsmentioning
confidence: 97%
See 2 more Smart Citations
“…This seems to indicate that θ a_occ could potentially be inferred from the optimum water content determined from the Standard Proctor test (ASTM D6-8 -12e2). However, for another substrate (fine sand) also successfully employed as MOL (Ndanga et al, 2015), Ahoughalandari et al (2018) found that the S r value associated with occlusion was greater than that given by the line of optima. As such, the simplification proposed, i.e.…”
Section: Design Steps Based On Hydraulic Considerationsmentioning
confidence: 97%
“…In the case of mineral soils, the MOL can be constructed in two sublayers: the vegetated top part (usually composed of humic topsoil, constituting the main rooting zone) and the subsoil. Examples of an topsoil-subsoil layering are given in Gebert et al (2003), biofilter;Huber-Humer et al (2009), biocover test cell; Bour et al (2015), laboratory column study; Gebert et al (2015), biowindow; Röwer et al (2016a), biocover andNdanga et al (2015); laboratory and field tests of several biofilters. The CH 4 oxidation front (depth) may vary over time, depending on the depth of ingress of atmospheric air, the composition and height of the accruing landfill gas, and the environmental conditions that drive the microbial process (e.g., temperature, water tension).…”
Section: Biocovermentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, various researchers have tested the most varied substrate materials (compost, sewage sludge, sand, garden waste, wood chips, expanded clay, etc. and their mixtures with the cover soil), biogas loading rates, climatic conditions, etc., always with the goal of studying and optimizing the methane oxidizing conditions in the land ll cover layer [6, 13,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation on a landfill's top cover may affect and be affected by LFG emissions, and irregularities in vegetation cover could indicate the presence of problematic spots. Plant roots can form channels and macropores in soil that facilitate O 2 diffusion and CH 4 supply to bacteria, stimulating CH 4 oxidation (Abichou et al, 2015, Ndanga et al, 2015. If the soil moisture content is sufficiently high, plant roots may also provide a favorable environment for CH 4 -oxidizing bacteria (Feng et al, 2017), which play a key role in reducing CH 4 emissions from landfills.…”
Section: Introductionmentioning
confidence: 99%